2014
DOI: 10.1038/srep07403
|View full text |Cite
|
Sign up to set email alerts
|

Vector modifications to eliminate transposase expression following piggyBac-mediated transgenesis

Abstract: Transgene insertion plays an important role in gene therapy and in biological studies. Transposon-based systems that integrate transgenes by transposase-catalyzed “cut-and-paste” mechanism have emerged as an attractive system for transgenesis. Hyperactive piggyBac transposon is particularly promising due to its ability to integrate large transgenes with high efficiency. However, prolonged expression of transposase can become a potential source of genotoxic effects due to uncontrolled transposition of the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…The piggyBac transposon system has been successfully used to create random insertion mutant mice 45 69 70 71 72 . However, methods of identifying mice with mutant insertions are not well established.…”
Section: Discussionmentioning
confidence: 99%
“…The piggyBac transposon system has been successfully used to create random insertion mutant mice 45 69 70 71 72 . However, methods of identifying mice with mutant insertions are not well established.…”
Section: Discussionmentioning
confidence: 99%
“…To create the construct needed for establishing a SSSavi stable expression line (HSB6G), we used Gateway cloning (Invitrogen) to insert dCas9-SSSavi and BirA into a piggyBac plasmid [61]. The dCas9-SSSavi was PCR amplified to include attB sites and then inserted into pDONR221 (Invitrogen) using BP clonase II (Thermo Fisher, #11789020) to create the pENTRY221_dCas9-SSSavi plasmid.…”
Section: Dcas9-sssavi Piggybac Plasmidmentioning
confidence: 99%
“…The consequence could be saltatory remobilization of the integrated transgene [43]. To limit the effect of sustained transposase expression, a self-inactivated transposase gene has been obtained by including either the promoter [44,45] or the polyadenylation signal [46] between the ITRs ( Table 1). Indeed, in primary human T cells, authors identified an active SB transposase ORF only in one clone out of 94, but a bulk analysis showed up to 0.047 transposase copy integrated per cell [50].…”
Section: Risk Of Transposase Gene Integrationmentioning
confidence: 99%